Nonexistence of solutions results for certain fractional differential equations - Berbiche, Mohamed (Mathematical Modelling and Analysis, 2011)
This paper is meant to establish sufficient conditions for the nonexistence of weak solutions to nonlinear fractional diffusion equation in space and time with nonlinear convective term. The Fujita exponent is determined.